The impact of educational intervention based on the theory of planned behavior on preventive behaviors for gastric cancer in obese and smoking individuals - Siamak Najafi; Fatemeh Mohammadkhah; Saina Alempour Salemi; Amirhossein Kamyab; Ali Khani Jeihooni (BMC Cancer)
Abstract Background Gastric cancer remains a significant global health issue due to its aggressive nature and high heterogeneity, making early detection and prevention critical. Obesity and smoking are established risk factors that significantly contribute to the development of gastric cancer. Despite the clear links between these risk factors and the disease, there is a lack of targeted educational interventions that address these behaviors. This study aims to fill this gap by investigating the impact of an educational intervention based on the Theory of Planned Behavior (TPB) on promoting preventive behaviors for gastric cancer among obese and smoking individuals. Methods This quasi-experimental study was conducted in 2021–2022 on 150 obese or overweight individuals, more than 25 years old who smoked (cigarettes and hookah) in Fasa city, Iran. From six urban health centers, two centers were randomly selected (one as the experimental group and the other as the control group). Data collection tools included a demographic characteristics questionnaire based on the TPB model (a researcher-made questionnaire). Based on pre-test results, the educational intervention for the experimental group included 12 educational sessions for 50 min, following the TPB model, through lectures, Question and Answers, group discussions, practical demonstrations, video clips, and PowerPoint presentations. The questionnaires were completed by both groups before and six months after the intervention. Data were analyzed using SPSS 22 and descriptive and analytical statistical methods (paired t- test, McNemar test, Chi-square test, and independent t-test) (p < 0.05). Results The results showed no significant difference between the two groups before the educational intervention. However, six months after the intervention, the experimental group showed a significant increase in TPB model cues (awareness, attitude, subjective norms, perceived behavioral control, behavioral intention, and behavior) (P < 0.001). Conclusion The findings of the present study indicate that the educational intervention based on the TPB model is useful in improving gastric cancer screening and preventive behaviors. It can also be used in planning and implementing appropriate programs to prevent and treat this disease.